Quadruple Helix Model for Women Migrant Workers Protection During Natural Disaster; learn from COVID-19 protection preparations - Aprillia, Bunga (Indonesian Journal of Social Science Research, 2024)
Cross-sectoral cooperation is urgently needed in the protection of women migrant workers. Especially migrant workers from West Java who are the third largest contributor in Indonesia after East Java and Central Java. The protection of women migrant workers requires a gender sensitive approach, because each protection will have a different impact on women and men. Natural disaster made the women migrant workers were affected economically, socially, and mentally. Cross-sectoral collaboration needs to be carried out by BP2MI, private companies providing employment, civil society represented by non-governmental organizations and mass media, and academics represented by researchers. Quadruple Helix theory by (Carayannis & Campbell, 2010) is an approach in creating a synergy of cooperation from four actors, namely A (Academician), B (Businessman), C (Civil Society) and G (Government) to build cross-sectoral collaboration in West Java. A qualitative research method with descriptive exposure was used in this study. The results of the study show that the actors involved in the protection of women migrant workers have shown cross-sectoral collaboration named Migrant Worker Resources Center one-stop service (LTSA- MRC) with gender sensitivity perspectives.